Persepsi Masyarakat terhadap Sanitasi Pasar Tradisional (Pasar Blimbing dan Pasar Mergan) di Kota Malang - Ainul Yaqin; Saimul Laili; Ahmad Syauqi (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2019)
Traditional market condition currently have cleanless image, especially in Malang district needed more attention to be reapired soon, if this not done immediately traditional market will be leaved by consumer alongside with the increasing amount of modern market. This research located at blimbing traditional market and mergan traditional market. The firts aim of this research to know condition of sanitation in both market, and the second aim to know society perception againts condition of sanitation in both market. Method of this research use quantitative descriptive and direct observation on field. Questionnaire is data collection technique that use to give some written question to respondent. In this research data source is market buyers in both market. determination of respondent sample use purposive sampling. Based on outcome research indicate sanitiation of blimbing and mergan traditional market still poor. This statetement based on the high of disagree answer on questionnaire.